757 The role of Kegel exercises in reducing involuntary loss of urine in Overactive Bladder and Mixed Urinary Incontinence (Balneo and PRM Research Journal, 2025)
Abstract: Objective: This study aimed to evaluate the efficacy of Kegel exercises, or pelvic floor muscle training (PFMT), in reducing symptoms of urinary incontinence among women with overactive bladder (OAB) and mixed urinary incontinence (MUI).Methods: A randomized control trial was conducted with a total of 50 participants (young women ages 18-35) out of which 35 were diagnosed with OAB and 15 with MUI. The participants were monitored for six months: In the first three months received only pharmacological therapy, solifenacin succinate 10 mg per day, and after this period the same group associated to the pharmacological treatment daily Kegel exercises. The primary outcome measured was the reduction in urinary incontinence episodes, while secondary outcomes included changes in quality of life (QoL) and bladder control as assessed by standardized questionnaires.After three months, group demonstrated a reduction in the frequency of urinary incontinence episodes. However, receiving both solifenacin succinate and Kegel exercises showed a statistically significant improvement in urinary control and QoL scores at six months evaluation.Conclusion: These findings suggest that the combination of pharmacological treatment with solifenacin succinate and Kegel exercises is more effective in managing urinary incontinence symptoms associated with OAB and MUI than pharmacological treatment alone. This approach may represent a beneficial strategy for patients requiring enhanced symptom relief.